CYTOTOXICITY EFFECT OF DOCETAXEL-LOADED-MICROEMULSION IN A549 NON-SMALL CELL LUNG CANCER AND HCT116 COLON CANCER CELLS - MAYSON H. ALKHATIB; WAFAA A. AL-QAIDI (International Journal of Pharma and Bio Sciences, 2014)
Docetaxel, an anti-mitotic chemotherapeutic agent, is mainly used for the treatment of various cancers. The objective of this study was to evaluate the antitumor activity of docetaxel-loaded-microemulsion in A549 non-small cell lung cancer and HCT 116 colon cancer cells. The safe effect of the formula was evaluated in HFS human foreskin cells. It has been found that the storage of the drug in the microemulsion formulation for around two weeks (O-ME) did not affect the toxicity of the drug formulations against the erythrocytes as the hemolysis activities of 1mg/ml of both of freshly prepared docetaxelloaded-microemulsion (F-ME) and O-ME were 36 ± 7.61 and 32.15 ± 6.32, respectively. The cytotoxicity screening revealed that 5µM of F-ME and O-ME were more cytotoxic than 5 µM of Taxotere by two folds when subjected unto A549 and HCT 116 cells and were less than 5 µM of Taxotere by approximately one and half folds when administered into HFS cells. Formulating the docetaxel in a microemulsion formula improved its efficiency besides reducing its side effect.